DIFFERENTIATION: ADDRESSING BIAS INVOLVED IN TEACHER CONFLICT WITH STUDENTS (Proceedings of the World Conference on Children and Youth, 2021)
The research purpose for this Literature review is to explore, and differentiate possible solutions for teacher-student conflict originating from teacher or student bias. The objective of this phenomenological literature review: to explore the reflective practice of teachers in relationship to differentiating possible solutions for teacher-student conflict created out of bias. The methodology includes aligning and subjugating five phenomenological areas of possible bias: personal choice, emotions, situations children experience, slow approaches to learning, and teacher reflection. A literature gap leaves research questions like; How does bias influence conflicts between teachers and students? How can reflection and differentiation make a difference in the bias that influences teacher conflicts with students? Reflection of personal biases allows educators to accept students’ values and unique perspectives, creating an example of non-biased educational environment. The exploration of teacher reflective practice, and attitudes; understanding personal biases allows for educators to accept students’ values and unique perspectives. The implications of educators’ awareness, reflection and responsiveness, to diverse student populations; includes students' social - emotional needs, trauma impact, cultural and economic backgrounds, and advocacy for equity and equality. Educators need to face personal biases recognizing the impact in the classroom where inequity and inequality can persist, influencing the development of conflict between teacher and student. The recommendation is for further phenomenological research on teacher and student opinion relating to how bias impacts teacher-student conflict, conducted in a current day environment, and continued for further assessment value.